Gender difference of intracerebral hemorrhage in young people: a clinical analysis of 88 cases - Han-wen ZHANG; Jin XU; Peng LI; Yue-chang YANG; Jian-mei XIONG; Zhen-yu LIU; Xiang-xiang ZHAO; Zhong-xin ZHAO (Chinese Journal of Contemporary Neurology and Neurosurgery, 2014)
The study retrospectively analyzed the clinical data of young people of different genders with intracerebral hemorrhage (ICH) in recent 5 years. There were 60 male and 28 female patients, and the ratio of men to women was 2.14∶1. During lots of risk factors for ICH, men had more smoking (35% vs 0, P = 0.000) and drinking history (28.33% vs 0, P = 0.002) than women, while women had more hyperlipidemia than men (10.71% vs 0, P = 0.030). For cerebral hemorrhage etiology, male patients who got ICH because of hypertension were more than female patients (40% vs 14.29%, P = 0.016), while female patients who got ICH due to cerebrovascular malformation were more than male patients (50% vs 23.33%, P = 0.012). The bleeding locations of men were mostly located in the basal ganglia (35% vs 14.29%, P = 0.045), while the bleeding locations of women were mostly located in the cerebral lobe (67.86% vs 40%, P = 0.015). The results suggested that there were gender difference in etiology, bleeding locations, and risk factors for ICH in young people.   doi: 10.3969/j.issn.1672-6731.2014.11.019